Usefulness of digital velcro crackles detection in identification of interstitial lung disease in patients with connective tissue diseases - Andreina MANFREDI; Giulia CASSONE; Caterina VACCHI; Fabrizio PANCALDI; Giovanni Della CASA; Stefania CERRI; Lisa De PASQUALE; Fabrizio LUPPI; Carlo SALVARANI; Marco SEBASTIANI (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the diagnostic accuracy of the VECTOR software in patients with connective tissue diseases (CTDs), compared with the reference standard of high-resolution computed tomography (HRCT). Patients and methods: The study included 98 consecutive patients of CTD (24 males, 74 females; median age 66 years; range, 24 to 85 years) with a recent HRCT. Patients were evaluated in a blindly manner by VECTOR and the results obtained by the algorithm were compared with the presence of interstitial lung disease (ILD) according to HRCT. Results: Interstitial lung disease was detected in 42.8% of subjects. VECTOR correctly classified 81/98 patients, with a diagnostic accuracy of 82.6%; sensitivity and specificity were 88.1% and 78.6%, respectively. Only 5/42 patients with ILD were not correctly classified by VECTOR, while false positive cases were 21.4%. No significant differences were observed according to the radiologic pattern of ILD. Conclusion: VECTOR showed high sensitivity, specificity and diagnostic accuracy, allowing selecting patients to be investigated with HRCT. The relatively high frequency rate of false positive results is acceptable if compared with the lack of effective screening methods for this complication of CTDs.